Hypoxic Conditioned Medium From Human Adipose‐Derived Stem Cells Promotes Mouse Liver Regeneration Through JAK/STAT3 Signaling - Sang Chul Lee (Stem Cells Translational Medicine, 2016)
Adipose‐derived stem cells (ASCs) mainly exert their function by secreting materials that are collectively termed the secretome. Despite recent attention to the secretome as an alternative to stem cell therapy, the culture conditions for generating optimal secretome contents have not been determined. Therefore, we investigated the role of hypoxic‐conditioned media (HCM) from ASCs. Normoxic‐conditioned media (NCM) and HCM were obtained after culturing ASCs in 20% O2 or 1% O2 for 24 hours, respectively. Subsequently, partially hepatectomized mice were infused with saline, control medium, NCM, or HCM, and then sera and liver specimens were obtained for analyses. Hypoxia (1% O2) significantly increased mRNA expression of mediators from ASCs, including interleukin‐6 (IL‐6), tumor necrosis factor α (TNF‐α), hepatocyte growth factor (HGF), and vascular endothelial growth factor (VEGF). HCM infusion significantly increased the number of Ki67‐positive cells in the liver (p < .05). HCM infusion significantly increased phospho‐signal transducer and activator of transcription 3 (STAT3) and decreased suppressor of cytokine signaling 3 (SOCS3) expression in the liver (p < .05). To determine the role of IL‐6 in liver regeneration, we then performed IL‐6 RNA interference study. Conditioned media (CM) obtained from ASCs, which were transfected with either siIL‐6 or siControl, were administered to partially hepatectomized mice. The siIL‐6 CM groups exhibited lower liver proliferation (Ki67‐positive cells) and markers of regeneration (protein expression of proliferating cell nuclear antigen, p‐STAT3, HGF, and VEGF and liver weights) than the siControl CM groups (p < .05). Taken together, hypoxic preconditioning of ASCs increased expression of mediators promoting anti‐inflammatory and regenerative responses. The liver regenerative effects of HCM appear to be mediated by persistent and uninhibited expression of STAT3 in the liver, which results from decreased expression of SOCS3. Significance In this study, it was found that treatment with the medium from hypoxic‐preconditioned adipose‐derived stem cells (ASCs) increased the viability of hepatotoxic hepatocytes and enhance liver regeneration in partially hepatectomized mice. In addition, the researchers first revealed that the hepatoprotective effects of hypoxic‐conditioned media are mediated by persistent and uninhibited expression of signal transducer and activator of transcription 3 in the liver, which result from a decreased expression of suppressor of cytokine signaling 3. Therefore, the hypoxic preconditioning of ASCs is expected to play a crucial role in regenerative medicine by optimizing the production of a highly effective secretome from ASCs.